PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP N 13 MERANGIN - Boni Candra; Ferinaldi; Sukur (Mat-Edukasia, 2019)
The purpose of this research is to find out and describe the students' ability to understand mathematical concepts using realistic mathematics education (RME) approach better than conventional learning. The study uses a quantitative approach with an experimental method. The study population was all students of class VIII SMP N 13 Merangin, amounting to four classes with a sample of class VIII C as an experimental class and class VIII B as a control class. The instruments used were test questions on the ability to understand mathematical concepts in the form of essays. The results of the data analysis requirements show that the data of the two sample classes are normally distributed and have homogeneous variances. Hypothesis testing uses the t-test formula. Based on the results of the analysis of research data shows that t arithmetic greater than t table or 2.401> 1.671 on a one-party test. Because t arithmetic> T table then Ho is rejected and Ha is accepted, so it can be concluded that the ability to understand mathematical concepts using realistic mathematics education (RME) approach is better than conventional learning of students of class VIII SMP N 13 Merangin.